Efektivitas Model Pembelajaran Kooperatif Tipe Jigsaw Untuk Meningkatkan Kemampuan Afektif Peserta Didik Kelas IV-B dan IV-D di SDN 154 Citepus Pajajaran Bandung - Mutia Nur Afifah (UNISBA Press, 2024)
Abstract. This study aims to examine: (a) how is the objective condition of the affective ability of fourth grade students before the implementation of the jigsaw cooperative model? (b) how is the implementation of the jigsaw cooperative model to improve the affective ability of fourth grade students? (c) how is the effectiveness of the implementation of the jigsaw cooperative model to improve the affective ability of students at SDN 154 Citepus Pajajaran Bandung? This study was motivated by the low affective ability of students, many students are still less active during learning, are embarrassed to express their opinions, the learning method is less interesting so that students become unfocused during learning, lack of discussion with fellow friends, one of the factors is because the learning method is monotonous and uninteresting, so that the learning atmosphere is not conducive and students become passive. This study uses a quantitative approach with a quasi-experimental method. This study is divided into two class groups, namely the experimental class (jigsaw cooperative learning method) and the control class (lecture learning model). The researcher used one of the quasi-experimental designs, namely the Nonequivalent Control Group Design. The results of this study, seen from observations and pretest posttest showed that there was an increase in students' affective abilities and there was a difference in the results of the pretest and posttest in the jigsaw learning method. While from the results of the questionnaire data there was no difference, and it was concluded that learning with the jigsaw method was not effective in improving students' affective abilities, it was more effective in improving students' cognitive aspects. Abstrak. Penelitian ini betujuan untuk mengkaji: (a) bagaimana kondisi objektif kemampuan afektif siswa siswa kelas IV sebelum diterapkannya model kooperatif tipe jigsaw? (b) bagaimana penerapan model kooperatif tipe jigsaw untuk mengingkatkan kemampuan afektif peserta didik kelas IV? (c) bagaimana efektivitas penerapan model kooperatif dengan tipe jigsaw untuk meningkatkan kemampuan afektif peserta didik di SDN 154 Citepus Pajajaran Bandung? Penelitian ini dilatarbelakangi oleh kemampuan afektif peserta didik yang masih rendah, banyak yang pasif ketika pembelajaran berlangsung, malu untuk mengeluarkan pendapat, metode pembelajaran kurang menarik sehingga membuat siswa menjadi tidak fokus saat pembelajaran, kurang diskusi dengan sesama teman, salah satu faktornya karena metode pembelajaran yang monoton serta tidak menarik, oleh karena itu suasana pembelajaran tidak kondusif dan siswa menjadi pasif. Penelitian ini menggunakan pendekatan kuantitatif dengan metode quasi eksperimen. Penelitian ini dibagi menjadi dua kelompok kelas, yaitu kelas eksperimen (metode pembelajaran kooperatif jigsaw) dan kelas kontrol (model pembelajaran ceramah). Peneliti menggunakan salah satu desain dari quasi experimental yaitu Nonequivalent Control Grup Design. Hasil dari penelitian ini, dilihat dari observasi dan pretes post test menunjukan bahwa ada peningkatan dalam kemampuan afektif peserta didik dan ada perbedaan hasil dari pretes dan postest pada metode pembelajaran jigsaw. Sedangkan dari hasil data angket tidak terdapat perbedaan, dan disimpulkan bahwa pembelajaran dengan metode jigsaw tidak efektif untuk meningkatkan kemapuan afektif peserta didik, lebih efektif untuk meningkatkan aspek kognitif peserta didik.